An enchanted modernity: Making sense of Latin America’s religious landscape - Morello SJ, Gustavo; Romero, Catalina; Rabbia, Hugo Hernán; Da Costa, Néstor (Critical Research on Religion)
This is an interpretative, critical, and selective review of scholarly contributions that explore Latin America’s religious landscape. We present data, both qualitative and quantitative, from Latin America and analyze the explanations given to make sense of it. After assessing the literature that uses either secularization theory or the “religious economy” approach, we study explanations that highlight a Latin American style of “popular religiosity.” These three models, in different ways, put the emphasis on religious institutions—their vitality, commands, competition, and authority. We propose, instead, a focus on the religious practices of regular believers. We speculate that embarking from that focus, the idea of an “enchanted modernity” will help make sense of Latin America’s religious landscape. Nuanced elucidation of Latin America’s religious particularities will situate them in dialogue with other regions of the world, like western Europe and the United States, while also acknowledging the fact that Latin America is experiencing a modernization process distinct from the North Atlantic one. Fil: Morello SJ, Gustavo. Boston College; Estados Unidos Fil: Romero, Catalina. Pontificia Universidad Católica de Perú; Perú Fil: Rabbia, Hugo Hernán. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Centro de Investigaciones y Estudio sobre Cultura y Sociedad. Centro de Investigaciones de la Facultad de Psicología - Grupo Vinculado CIPSI; Argentina Fil: Da Costa, Néstor. Universidad Catolica de Uruguay; Uruguay